The effects of replacement of soybean meal by shrimp shell meal on the growth of hybrid tilapia (Oreochromis niloticus x Oreochromis aureus) reared under brackish water (African Journal of Fisheries Science, 2022)
To evaluate the effects of complete replacement of soybean meal (SBM) protein by shrimp shell meal (SSM) on the growth performance of hybrid tilapia (O. niloticus x O. aureus), five approximately isoenergetic and isonitrogenous (30% crude protein) diets containing 0, 33, 50, 67 and 100% SSM were fed to triplicate groups of ten fry with an initial mean weight 1.54 ± 0.03 g/fish under brackish water (15 ppt) for sixty (60) days. Fish fed diet containing 100% SSM exhibited the lowest specific growth rate (SGR). There was no significant difference of SGR in the fish fed 0, 33, 50 and 67% SSM. The fish fed 0, 33 and 50% SSM had better feed conversion rate (FCR) value than those fish fed with 67 and 100% SSM supplement. The survival of juveniles ranged from 97 to 100%, being 97% for 0, 50, 67% SSM and 100% for 33 and 100% SSM. The weight gain was highest in fish fed diet without SSM, intermediate in fish fed diets with 33, 50 and 67% SSM, and lowest in fish fed diet with 100% SSM. The highest body protein content was observed in fish fed diets with 50 and 67% SSM compared to the initial fish. The lowest body protein content was obtained with the fish fed diet with 100% SSM. The tilapia fed diet containing 33 and 67% SSM had the highest body lipid content compared to the initial fish. There were no significant differences in body lipid content among the fish fed diet with 0, 50 and 100% SSM. No difference in body ash content was observed among treatments.